The Use of Storybird Platform to Arise Students’ Interest in Writing Recount Text - Fabella Ulfiantari; Rahayu Aprialiaswati (FKIP - Universitas Tanjungpura, 2023)
Students' behavior during the learning process was influenced by interest. This study used the Storybird platform as a media tool in the classroom to examine students' interest in authoring recount texts. 35 students from an SMPN Pontianak participated in this study. The observation checklist, field notes, interview, and writing test were the instruments employed in this research, which was a classroom action study. It was conducted in two cycles. The results demonstrated that using the Storybird platform to train students to write recount texts stimulated their enthusiasm in addition to their writing abilities. In their writing lesson, the students were more engaged, enthusiastic, motivated, and confident. They enjoyed writing recount text and followed the learning activities. According to the indicators of interest, the increase in student interest over the previous cycle ranged from 83% to 100%. Additionally, it improved the students’ writing skills. The quantitative data show that the students' cycle 1 test score was 72.18, and their cycle II exam score was 80.03.